Correlation of Turonian continental margin and deep-sea sequences in the subtropical Indian Ocean sediments by integrated planktonic foraminiferal and calcareous nannofossil biostratigraphy - B. Huber; D. Watkins; S. Haynes; K. Macleod; M.R. Petrizzo (Newsletters on Stratigraphy, 2017)
Marine mudstone sediments recovered from multiple boreholes drilled in southeast Tanzania yield some of the best preserved Turonian microfossils in the world, and these specimens provide a valuable new perspective on planktonic foraminiferal and calcareous nannofossil evolution, taxonomy, biostratigraphy, and biodiversity. High sedimentation rates and the consistent presence of well-preserved microfossil assemblages throughout the sequence increase the resolution of biostratigraphic data generated allowing for improved correlation within and outside the depositional basin. The late early middle Turonian Tanzanian record reveals prolonged species stasis with essentially no changes in relative abundance, no extinctions, and no evolutionary appearances for both calcareous plankton groups until the late middle Turonian. This interval is followed in the late Turonian by two species turnovers. The older of these occurs at the top of the mid-Turonian Helvetoglobotruncana helvetica Zone, where last occurrences of three planktonic foraminiferal species are followed, within several meters, by first occurrences of five foraminiferal species and an increase in the abundance of dwarfed planktonic forms. Changes in the calcareous nannofossil assemblages at this level are modest and include the extinction of one calcareous nannofossil species and an abrupt but temporary spike in the abundance of another species. There are no obvious changes in lithology, bulk sediment geochemistry, or stable isotope values across this first turnover event. The second, larger species turnover occurs at a hiatus within the late Turonian Marginotruncana sinuosa-Huberella huberi Zone and is marked by extinction of three calcareous nannofossil species followed by first appearances of four calcareous nannofossil species. Corresponding with the nannofossil first occurrences is a dramatic increase in the relative abundance of several species of biserial planktonic foraminifera, an increase in average grain size, and a shift in preservation such that ...